2012
DOI: 10.1177/1420326x12443246
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Air-conditioning Usage on Sick Building Syndrome during Summer in China

Abstract: The air-conditioned thermal environments can have an important impact on human health. People stay in airconditioned environments for a long period of time would tend to present weakened thermal adaptation and have weaker ability to endure hot environment, hence increasing the risk burden caused by heat stress on their physiological regulations to cause discomfort. In this study the relationship between human healtha prevalence of Sick Building Syndrome (SBS) -and air-conditioned indoor environment in summer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 9 publications
0
13
0
2
Order By: Relevance
“…This high prevalence of discomfort among AC users who spent a considerable amount of time indoors (in the AC environment) might be due the effect of prolonged AC exposure on their thermal adaptation. The works of Cao et al [25] revealed that people who tend to stay for a long period of time in an air-conditioned environment tend to have weakened thermal adaptation and have weaker ability to endure hot environment. Graudenz et al [26] also reported that people spend 80-90% of their time indoors, and indoor environments have important effects on the human health.…”
Section: Discussionmentioning
confidence: 99%
“…This high prevalence of discomfort among AC users who spent a considerable amount of time indoors (in the AC environment) might be due the effect of prolonged AC exposure on their thermal adaptation. The works of Cao et al [25] revealed that people who tend to stay for a long period of time in an air-conditioned environment tend to have weakened thermal adaptation and have weaker ability to endure hot environment. Graudenz et al [26] also reported that people spend 80-90% of their time indoors, and indoor environments have important effects on the human health.…”
Section: Discussionmentioning
confidence: 99%
“…With reference to the role played by the air-conditioning systems, recently (Sun et al, 2011) proposed a quite new control strategy for multi-zone VAV HVAC systems (i.e., variable air volume), suitable to guarantee both adequate indoor air quality and energy savings. In the same direction, the paper (Cao et al, 2013) evidences that an excessive use of air-conditioning has negative effects: …”
Section: Hospitals and Air-conditioningmentioning
confidence: 97%
“…Factors indicated as possible causes include physical parameters (temperature, humidity, ventilation, particle matters, etc.) and psychological issues (Cao et al, 2012). In general, buildingrelated symptoms refer to the prevalence of general, mucosal, skin symptoms which were associated with eyes, nose, and upper respiratory, and skin (Eriksson and Stenberg, 2006).…”
Section: Building-related Symptomsmentioning
confidence: 99%
“…The health of people working inside air-conditioned offices depends on biological, chemical, and thermal variables (Turiel, 1998). A study conducted in the tropical climate zones of China indicated that extended exposure to air-conditioned environments may cause discomfort to the human body, although a few people were more comfortable in such cool air-conditioned environments (Cao et al, 2012). Furthermore, the probability of sick building syndrome can be higher if thermal variables, such as ambient temperature, relative humidity (RH), and ventilation rate, are not controlled appropriately (Amin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%